Aromatics production from fast co-pyrolysis of lignin and waste cooking oil catalyzed by HZSM-5 zeolite. (1st April 2020) - Fan, Liangliang; Ruan, Roger; Li, Jun; Ma, Longlong; Wang, Chenguang; Zhou, Wenguang
Graphical abstract: Highlights: The co-pyrolysis of lignin and waste cooking oil yielded up to 82.6% mono-aromatics. The highest synergistic extent for mono-aromatic production was 52.1%. Lignin-derived model compounds were selected for co-pyrolysis to study the mechanism. Guaiacol was more active to be converted to aromatics than o -cresol and phenol. The mechanism of catalytic co-pyrolysis of lignin and waste cooking oil was proposed. Abstract: Lignin and waste cooking oil are wastes from paper and food industries, respectively. In this work, the catalytic fast co-pyrolysis of lignin and waste cooking oil for the production of aromatics in a pyroprobe was investigated with an aim to improve the utilization of lignin waste and waste cooking oil. Furthermore, lignin-derived monomers, including phenol, o -cresol, and guaiacol, were also used as model feedstock for the catalytic co-pyrolysis in order to study the mechanism underlying aromatic formation. The mechanistic study helped lay theoretical foundation for the industrial application of the co-pyrolysis process. The effects of catalyst and waste cooking oil addition on co-pyrolysis product fractional yield and selectivity were studied. High amount of waste cooking oil in the feedstock with appropriate catalyst-to-feedstock ratio (3:1) contributed to high peak-area yields of the total detected compounds and aromatics. The alkylation and demethoxylation of phenols were enhanced at high ratios of catalyst to feedstock and waste cooking oil to lignin. When the ratio of waste cooking oil to lignin was 1:1, the highest mono-aromatic selectivity (82.6%) and synergistic extent (52.1%) for mono-aromatic production were obtained. The catalytic co-pyrolysis of the lignin-derived monomers and waste cooking oil showed that guaiacol was the most active compound to be converted to aromatics, followed by o -cresol, and phenol. The reaction mechanism underlying the formation of aromatics from the synergistic conversion of aliphatics and phenolics was elaborated.